IDENTIFIKASI FAKTOR PREDIKTOR SINDROM METABOLIK PADA PASIEN RAWAT JALAN - Cui, Zhan; Wienaldi, Wienaldi; Liena, Liena (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Metabolic syndrome is a collection of metabolic risk factors that increase the likelihood of cardiovascular disease, type 2 diabetes mellitus, and various other chronic complications. This study aims to analyze factors associated with the incidence of metabolic syndrome in outpatients at the Internal Medicine Clinic of Royal Prima Hospital in Medan in 2025. This study used an analytical observational design with a quantitative approach and a cross-sectional design. The study sample consisted of 96 patients selected using purposive sampling. Data collection was conducted through medical records and questionnaires to obtain information on the demographic characteristics, anthropometry, physical activity, and dietary patterns of the respondents. Data analysis was performed univariately, bivariately using the Chi-square test, and multivariately using logistic regression to determine the most dominant factors. The results showed that 49 patients (51.0%) had metabolic syndrome. Bivariate analysis showed that age ≥45 years, body mass index (BMI) ≥25 kg/m², high waist circumference, light physical activity, and unhealthy eating patterns were significantly associated with the occurrence of metabolic syndrome, while gender did not show a significant association. Multivariate analysis showed that waist circumference was the most dominant factor with an odds ratio (OR) of 4.14. These results indicate that abdominal obesity is an important factor in the occurrence of metabolic syndrome. Therefore, prevention efforts should focus on controlling waist circumference through increased physical activity and the implementation of a healthy diet.